PENETAPAN AWAL BULAN QAMARIYAH PERSPEKTIF FIQH - Iman RN., Bustanul (DIKTUM: Jurnal Syariah dan Hukum, 2016)
The focus of the study in this paper is the system of setting early qamariyah both methodologically and practically in determining the positioning of when and where the beginning of the day. By using the approach fiqhiyyah concluded: By using the approach fiqhiyyah concluded: First, there are two methods used in the determination of the beginning of the month qamariyah, namely (a) the rukyat method. (B) the hisab method. The hisab method there are two notions, namely hisab haqiqi wujûd al-hilâl and hisab imkân al-ru'yat. Second, the determination of positioning when and where the beginning of the day. There are three opinions: (1) The day begins at sundown (the majority view); (2) The day begins at the dawn (the minority view), and (3) The day starts at midnight (00:00 hours, a new view). As to where the beginning of the day there are two views: (a) is positioned 180 ° from Mecca; and (b) are placed at 180 ° from GMT.